ANTIMICROBIAL ACTIVITY OF WHOLE PLANT OF LUFFA CYLINDRICA (LINN) AGAINST SOME COMMON PATHOGENIC MICRO-ORGANISMS (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
In this present investigation was to evaluate the antimicrobial activity of pet ether and chloroform extract of whole plant of Luffa cylindrica (Linn) by in-vitro method in agar plate against ten bacterial and four fungal species. The extract was prepared from the whole plant of Luffa cylindrica (Linn) by hot continuous percolation method in Soxhlet apparatus with various solvents (Pet ether & Chloroform). The minimum inhibitory concentration of the various extract range from 266.66µg/ml to 66.66µg/ml on tested bacteria and fungai. The maximum antibacterial activity of chloroform extract of whole plant of Luffa cylindrica (Linn) was found at 200.00µg/ml than that of petroleum ether extract. The significant antifungal activity of chloroform extract was found at 266.66µg/ml than that of petroleum ether extract. The antimicrobial activity was showed at concentration dependent. The results of the above study clearly indicated that the chloroform extract of whole plant of Luffa cylindrica (Linn) was found significant antibacterial and antifungal activity which might be helpful in preventing the progress of various diseases and can be used in alternative system of medicine.